Early-strength quick-hardening efficient carbon sequestration regenerated pervious concrete and preparation method thereof
By combining regenerated aggregate treatment and multiple curing, early-strength, fast-hard, high-efficiency carbon-solid and recycled permeable concrete is prepared, which solves the problems of low strength and poor durability of permeable concrete in the early stage, and achieves efficient carbonization and strength improvement.
Patent Information
- Application Number
- CN202411839915.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
AI Technical Summary
The existing permeable concrete has low strength and poor durability in the early stage, and the mechanical properties and durability of permeable concrete after carbonization curing are lower than those of permeable concrete without carbonization curing.
Recycled aggregates are used to prepare early, fast and hard, high-efficiency carbon-solid and recycled permeable concrete. By crushing, grinding and placing waste concrete aggregates into saturated lime water and calcium oxide powder, recycled aggregates covering calcium oxide are formed, and combined with components such as cementitious materials, cellulose ether, defoaming agent and dispersible latex powder, carbonization is carried out through multiple curing combinations.
It significantly improves the early strength and durability of permeable concrete, improves carbon sequestration efficiency and strength enhancement effect, and ensures efficient carbonization and long-lasting performance of permeable concrete.
Smart Images

Figure CN119707410A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of permeable concrete, and specifically relates to an early-strength, fast-hardening, high-efficiency carbon-fixing and regenerating permeable concrete and a preparation method thereof. Background Art
[0002] Carbonized cement-based materials can achieve the purpose of large-scale utilization of CO2. However, the premise of efficient carbonization of cement-based materials requires that the material itself has a channel for CO2 gas transmission, and sufficient calcium source inside the material is also a necessary condition for efficient carbonization. The carbonization reaction of cement-based materials requires suitable humidity conditions and better internal composition. At present, existing studies have mostly adopted conventional carbonization conditions to directly carbonize permeable concrete of different compositions. Insufficient contact between CO2 and permeable concrete and insufficient absorption of CO2 by raw materials result in low carbon fixation efficiency of permeable concrete, and the strength of permeable concrete after carbonization curing is small. In addition, due to the lack of full consideration of the mechanism of action of CO2 curing cement-based materials, the mechanical properties and durability of permeable concrete that has undergone early carbonization curing are even lower than those of permeable concrete that has not been carbonized when it continues to be cured to the middle and late stages.
[0003] Recycled aggregate concrete made from recycled aggregate is a green and environmentally friendly building material and one of the effective ways to efficiently deal with construction waste. Driven by the concept of sustainable development, recycled aggregate concrete is being used on a large scale in my country.
[0004] Permeable concrete, also known as porous concrete, is generally a double-layer structure of surface mortar and bottom macroporous concrete, mainly composed of cement, water, coarse aggregate, and no fine aggregate. The strength of permeable concrete mainly depends on the strength of cement slurry and aggregate. In recent years, a large number of scholars have placed recycled aggregate or concrete in a specific CO2 environment to achieve the effect of accelerated carbonization. The carbonization of recycled aggregate can increase the strength of the old mortar attached to the recycled aggregate, and improve the performance of recycled concrete by improving the performance of the aggregate.
[0005] At present, most of the carbonized concrete is directly carbonized without fully considering the interaction between CO2 and cement-based materials, resulting in low carbonization efficiency and high consumption of CO2. 2, However, the carbonization effect is general and the effect of improving the strength of concrete is also weak.
[0006] Patent CN 10928421 B discloses a method for preparing prefabricated permeable concrete cured with carbon dioxide, which comprises mixing various raw materials, molding them into a mold, and transferring them into a carbon fixation chamber for curing until the curing time is over. The patent proposes the concept of carbon fixation in prefabricated permeable concrete. However, the patent aims to directly carbonize concrete of various compositions, without fully considering whether the concrete is fully exposed to carbon dioxide and the mechanism of action of carbon dioxide and cement-based materials, the relatively low carbon dioxide concentration and the short curing time. Summary of the invention
[0007] Purpose of the invention: The technical problem to be solved by the present invention is to provide a permeable concrete prepared with recycled aggregate and a preparation method thereof in view of the deficiencies in the prior art, which solves the problems of low early strength and poor durability of permeable concrete, and provides an effective technical approach for energy conservation, carbon reduction and efficient treatment of construction waste.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows: An early-strength, fast-hardening, high-efficiency carbon-fixing and regenerating permeable concrete, made from the following components in parts by mass: 100~160 parts of recycled aggregate, 30~40 parts of binder, 18~19 parts of water, 0.36~1.08 parts of cellulose ether, 0.36~0.72 parts of defoamer, 0.36~3.6 parts of dispersible latex powder and 1.8~2.88 parts of early strength seed; The binder is composed of ordinary Portland cement and sulphoaluminate cement in a mass ratio of 2 to 3:1; The mass ratio of the recycled aggregate to the binder is controlled at 3-5:1.
[0009] Preferably, the composition comprises 140 parts of recycled aggregate, 25.2 parts of ordinary Portland cement, 10.8 parts of sulphoaluminate cement, 19 parts of water, 0.36 parts of cellulose ether, 0.36 parts of defoamer, 0.36 parts of dispersible latex powder and 2.88 parts of early strength seed crystals.
[0010] Specifically, the recycled aggregate is crushed recycled concrete aggregate, the particle size of the recycled aggregate is between 5 and 16 mm, and the preparation method is: crush and grind the waste concrete aggregate, pass it through a square hole sieve with an aperture of 4.75 to 9.5 mm, place it in saturated lime water until the saturated surface is dry, and then put the surface-dry concrete aggregate into calcium oxide powder, and mix it thoroughly so that the surface of the concrete aggregate is evenly covered with calcium oxide. This method can allow more calcium sources inside the binder, providing a sufficient way for the efficient solidification of CO2 in permeable concrete.
[0011] Specifically, the ordinary Portland cement is graded P.II 52.5R and has a specific surface area of 300-400 m 2 kg-1 The sulphoaluminate cement has a grade of 525 and a specific surface area of 400-500 m 2 kg -1 .
[0012] Specifically, the cellulose ether is hydroxyethyl methyl cellulose, with a viscosity of 35000-45000 MPa·s and an average particle size of 10-12 μm.
[0013] Specifically, the defoamer is a silicone modified defoamer, model number RE 2971, in the form of milky white powder with an average particle size of 18-20 μm.
[0014] Specifically, the dispersible latex powder is ethylene-vinyl acetate latex powder, and the average particle size is 80-90 μm.
[0015] Specifically, the early strength seed crystal is a CSH seed crystal suspension, the calcium-silicon molar ratio is 0.9-1, and the solid content of the suspension is 20-25 wt%.
[0016] Furthermore, the present invention also provides a method for preparing the above-mentioned early-strength, fast-hardening, efficient carbon-fixing and regenerating permeable concrete, comprising the following steps: (1) After crushing, grinding and sieving the waste concrete aggregate, the waste concrete aggregate is placed in saturated lime water until the surface is dry. The dry concrete aggregate is then placed in calcium oxide powder and mixed thoroughly so that the surface of the concrete aggregate is evenly covered with calcium oxide to obtain recycled aggregate; (2) mixing ordinary Portland cement and sulphoaluminate cement uniformly to obtain a binder; (3) Mix the binder and 1 / 2 to 2 / 3 of the total water volume and stir evenly, then add cellulose ether, dispersible latex powder and early strength seed crystals in sequence, and continue stirring for 1 to 5 minutes; (4) Add the remaining water and recycled aggregate, mix well, put into the mold, vibrate and compact, and transfer the mold into a closed curing room for curing for 6 to 12 hours; (5) After curing, demoulding is performed, and the specimen is placed in a carbonization kettle and carbonized with carbon dioxide gas. After carbonization, the specimen is placed in water for curing. By selecting an appropriate pre-curing time, the permeable concrete that has undergone early carbonization curing is placed in water for curing, providing suitable humidity conditions for the hydration of cement paste inside the carbonized layer of the permeable concrete, which is conducive to the growth of later strength.
[0017] Preferably, in step (4), the relative humidity in the closed curing room is 90-100% and the temperature is 18-22°C.
[0018] Preferably, in step (5), the mass fraction of carbon dioxide gas in the carbonization kettle is 90-100%, the carbonization pressure is 0.3-0.8 MPa, and the carbonization time is 2-6 h. Beneficial Effects
[0019] (1) The present invention pre-treats waste concrete aggregates by soaking the aggregates in saturated lime water, taking them out and drying them on a saturated surface, at which time the surface of the aggregates is covered with calcium hydroxide. Calcium oxide is then used to fully wrap the aggregates, at which time the surface of the aggregates is covered with calcium hydroxide and calcium oxide. During the concrete making process, calcium oxide reacts with water to form calcium hydroxide. During subsequent carbonization, CO2 reacts with calcium hydroxide to form more calcium carbonate, providing a way for permeable concrete to absorb CO2 efficiently. Adding cellulose ether and dispersible latex powder has an air entraining effect on concrete, which increases the porosity inside the permeable concrete and increases the number of pores, providing sufficient space for the permeable concrete to contact with CO2.
[0020] (2) The present invention adopts a combination of multiple curing methods, selects a suitable pre-curing time, and places the permeable concrete that has undergone early carbonization curing in water for curing, thereby providing suitable humidity conditions for the hydration of the cement paste inside the carbonized layer of the permeable concrete, thereby facilitating the growth of later strength.
[0021] (3) The present invention takes into account the humidity conditions of the cement paste of the permeable concrete, effectively improves the reaction rate of CO2 gas and cement paste, can achieve rapid demoulding of the permeable concrete, and significantly improves the process of rapid absorption of CO2 by the permeable concrete.
[0022] (4) Based on the pore structure of cement-based materials and the penetration mechanism of CO2 gas, the present invention uses a variety of admixtures to collaboratively construct the micro-nano pore structure of cement paste on the aggregate surface, so that CO2 gas can effectively penetrate into the surface and interior of permeable concrete. Furthermore, the outside and inside of the cement paste can fully react with CO2, thereby improving the carbon fixation efficiency of permeable concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0024] Figure 1 1 is the XRD spectrum of the permeable concrete obtained before and after carbonization in Example 1. Wherein, a is the curing age of 3 days, and b is the curing age of 28 days.
[0025] Figure 2 : is the infrared spectrum of the permeable concrete obtained before and after carbonization in Example 1. Wherein, a is the 3 d curing age, and b is the 28 d curing age.
[0026] Figure 3The following are scanning electron microscope images of the uncarbonized and carbonized slurry of Example 1 after 3 and 28 days of curing. (a) is the uncarbonized slurry after 3 days of curing, (b) is the carbonized slurry after 3 days of curing, (c) is the uncarbonized slurry after 28 days of curing, and (d) is the carbonized slurry after 28 days of curing; (e) is the EDS analysis result of point 1. DETAILED DESCRIPTION
[0027] The present invention can be better understood with reference to the following examples.
[0028] In the following examples, waste concrete aggregate is crushed and ground, passed through a square hole sieve with an aperture of 4.75 to 9.5 mm, to obtain fine concrete aggregate powder, which is then placed in saturated lime water until saturated surface dry, and then the surface dry concrete aggregate is placed in calcium oxide powder, mixed thoroughly so that the surface of the concrete aggregate is evenly covered with calcium oxide, and then placed in water until saturated surface dry to obtain recycled aggregate.
[0029] The grade of ordinary Portland cement is P.Ⅱ 52.5R, and its specific surface area is 373 m 2 kg -1 The sulphoaluminate cement has a grade of 525 and a specific surface area of 406 m 2 kg -1 .
[0030] The cellulose ether is hydroxyethyl methyl cellulose with a viscosity of 15000 mPa·s and an average particle size of 11.1 μm.
[0031] The defoamer is a silicone modified defoamer, model number RE 2971, in the form of milky white powder with an average particle size of 19.7 μm.
[0032] The dispersible latex powder is ethylene-vinyl acetate latex powder, and the average particle size is 85 μm.
[0033] The early strength seed crystal is CSH seed suspension, the calcium-silicon molar ratio is 0.947, and the solid content of the suspension is 20.7 wt%. Example 1
[0034] The formula of the carbon fixation regeneration permeable concrete in this embodiment is as follows (10g is 1 portion): 140 parts of recycled aggregate, 25.2 parts of ordinary Portland cement, 10.8 parts of sulphoaluminate cement, 19 parts of water, 0.36 parts of cellulose ether, 0.36 parts of defoaming agent, 0.36 parts of dispersible latex powder, and 2.88 parts of early-strength seed crystals.
[0035] The preparation process is as follows: (1) After sieving the waste concrete aggregate, place it in saturated lime water until the saturated surface is dry, then place the surface-dry concrete aggregate into calcium oxide powder and mix them thoroughly so that the surface of the concrete aggregate is evenly covered with calcium oxide to obtain recycled aggregate; (2) mixing ordinary Portland cement and sulphoaluminate cement uniformly to obtain a binder; (3) Mix the binder and 53% of the total water volume and stir evenly, then add cellulose ether, dispersible latex powder and early strength seed crystals in sequence, and continue stirring for 1 to 5 minutes; (4) Add the remaining water and recycled aggregate, mix well, put into the mold and vibrate it, and then transfer it to a closed curing room for curing for 6 hours. The relative humidity in the closed curing room is 95% and the temperature is 18~22℃.
[0036] (5) After curing, demold the specimens and place them in a carbonization kettle for carbonization. After carbonization, place them in water for curing. De-mold the other specimens and place them in water for 2 h for curing. Set the blank control group as the control group. The mass fraction of carbon dioxide in the carbonization kettle was controlled to be 95%, the carbonization pressure was 0.3 MPa, and the carbonization time was 2 h.
[0037] Figure 1 The XRD spectra of the uncarbonized and carbonized slurry of Example 1 after subsequent curing for 3 days and 28 days. As shown in Figure (a), when the slurry is cured for 3 days, the main hydration products after carbonization are AFt, Ca(OH)2 and CaCO3. And the diffraction peak intensity corresponding to CaCO3 is increased after carbonization, especially in the range of 2θ of 25° to 30°, the diffraction peak intensity of CaCO3 is the largest, while the intensity of the diffraction peak corresponding to the unhydrated minerals C3S and C2S after carbonization is significantly reduced. As shown in Figure (b), when the slurry is cured for 28 days, it can be seen that the diffraction peak intensity of Ca(OH)2 is significantly increased in the uncarbonized slurry, and the diffraction peak intensity corresponding to the minerals C3S and C2S is significantly reduced, which indicates that the degree of cement hydration gradually increases with the extension of the hydration time of the slurry. In addition, compared with the uncarbonized pure paste, after carbonization curing, the diffraction peak intensity of Ca(OH)2 decreased significantly, while the diffraction peak intensity corresponding to CaCO3 increased significantly. This shows that carbonization promotes the generation of CaCO3. It can be seen that carbonization promotes the reaction of Ca(OH)2 and CO2, increasing the content of CaCO3, both at 3 days and 28 days, which provides conditions for improving the strength of permeable concrete.
[0038] Figure 2 The infrared spectra of the uncarbonized slurry and the carbonized slurry of Example 1 after subsequent curing for 3 days and 28 days. 1416cm -1The absorption peak at 1416cm is related to the presence of CaCO3. -1 The absorption peak intensity increased significantly, indicating that the CaCO3 content increased significantly after carbonization. -1 The absorption peak intensity increases significantly, so the CaCO3 content after carbonization is relatively high. This shows that carbonization promotes the formation of CaCO3, and sufficient CaCO3 contributes to the high strength of permeable concrete.
[0039] Figure 3 The SEM images of Example 1 after the uncarbonated curing and subsequent curing of the carbonized slurry at 3 and 28 days are shown in Table 1. The EDS analysis results of point 1 in the SEM image are shown in Table 1. As can be seen from the figure, when the curing is 3 and 28 days, hydration products such as CSH gel, calcium sulfonate and Ca(OH)2 can be seen inside the cement paste. Combined with the EDS analysis results, it can be seen that when the curing continues to 28 days after carbonization, a certain amount of CaCO3 is contained inside the cement paste. CaCO3 can effectively fill the pores of different sizes inside the cement paste, providing strong support for the improvement of the strength of permeable concrete.
[0040] Table 1 Example 2
[0041] The formula of the carbon fixation regeneration permeable concrete in this embodiment is as follows (10g is 1 portion): 140 parts of recycled aggregate, 30.6 parts of ordinary Portland cement, 5.4 parts of sulphoaluminate cement, 19 parts of water, 0.72 parts of cellulose ether, 0.36 parts of defoaming agent, 1.8 parts of dispersible latex powder, and 2.88 parts of early-strength seed crystals.
[0042] The preparation process is as follows: (1) After sieving the waste concrete aggregate, place it in saturated lime water until the saturated surface is dry, then place the surface-dry concrete aggregate into calcium oxide powder and mix them thoroughly so that the surface of the concrete aggregate is evenly covered with calcium oxide to obtain recycled aggregate; (2) mixing ordinary Portland cement and sulphoaluminate cement uniformly to obtain a binder; (3) Mix the binder and 53% of the total water volume and stir evenly, then add cellulose ether, dispersible latex powder and early strength seed crystals in sequence, and continue stirring for 1 to 5 minutes; (4) Add the remaining water and recycled aggregate, mix well, put into the mold and vibrate it, and then transfer it to a closed curing room for curing for 6 hours. The relative humidity in the closed curing room is 95% and the temperature is 18~22℃.
[0043] (5) After curing, demould and place the specimen into a carbonization kettle for carbonization. After carbonization, place the specimen into water for curing. The mass fraction of carbon dioxide in the carbonization kettle was controlled to be 100%, the carbonization pressure was 0.5 MPa, and the carbonization time was 4 h. Example 3
[0044] The formula of the carbon fixation regeneration permeable concrete in this embodiment is as follows (10g is 1 portion): 140 parts of recycled aggregate, 33.1 parts of ordinary Portland cement, 2.88 parts of sulphoaluminate cement, 19 parts of water, 1.08 parts of cellulose ether, 0.72 parts of defoaming agent, 3.6 parts of dispersible latex powder, and 2.88 parts of early-strength seed crystals.
[0045] The preparation process is as follows: (1) After sieving the waste concrete aggregate, place it in saturated lime water until the saturated surface is dry, then place the surface-dry concrete aggregate into calcium oxide powder and mix them thoroughly so that the surface of the concrete aggregate is evenly covered with calcium oxide to obtain recycled aggregate; (2) mixing ordinary Portland cement and sulphoaluminate cement uniformly to obtain a binder; (3) Mix the binder and 53% of the total water volume and stir evenly, then add cellulose ether, dispersible latex powder and early strength seed crystals in sequence, and continue stirring for 1 to 5 minutes; (4) Add the remaining water and recycled aggregate, mix well, put into the mold and vibrate it, and then transfer it to a closed curing room for curing for 6 hours. The relative humidity in the closed curing room is 95% and the temperature is 18~22℃.
[0046] (5) After curing, demould and place the specimen into a carbonization kettle for carbonization. After carbonization, place the specimen into water for curing. The mass fraction of carbon dioxide in the carbonization kettle was controlled to be 100%, the carbonization pressure was 0.8 MPa, and the carbonization time was 6 h.
[0047] Comparative Example The formula of the carbon fixation regeneration permeable concrete in this embodiment is as follows (10g is 1 portion): 140 parts of concrete aggregate fine powder (not soaked in saturated lime water and not covered with calcium oxide powder), 25.2 parts of ordinary Portland cement, 10.8 parts of sulphoaluminate cement, 19 parts of water, and 2.88 parts of early strength seed crystals.
[0048] The preparation process is as follows: (1) Screening the waste concrete aggregate; (2) mixing ordinary Portland cement and sulphoaluminate cement uniformly to obtain a binder; (3) Mix the binder and 53% of the total water volume and stir evenly, then add cellulose ether, dispersible latex powder and early strength seed crystals in sequence, and continue stirring for 1 to 5 minutes; (4) Add the remaining water and recycled aggregate, mix well, put into the mold and vibrate it, and then transfer it to a closed curing room for curing for 6 hours. The relative humidity in the closed curing room is 95% and the temperature is 18~22℃.
[0049] (5) After curing, demould and place the specimen into a carbonization kettle for carbonization. After carbonization, place the specimen into water for curing. The carbonization kettle has a carbon dioxide mass fraction of 95%, a carbonization pressure of 0.3 MPa, and a carbonization time of 2 h.
[0050] Table 2 shows the performance evaluation indexes of various embodiments and comparative examples, which are implemented with reference to CJJ / T135-2009 "Technical Specifications for Permeable Cement Concrete Pavement", GB / T12988 "Test Method for Wear Resistance of Inorganic Ground Materials", and GB / T50082 "Test Method for Long-term Performance and Durability of Ordinary Concrete". As can be seen from Table 2, the permeable concrete prepared by the present invention has high strength, good wear resistance, good durability, and good water permeability.
[0051] Comparing Example 1 with the comparative example, it can be learned that the permeable concrete made by soaking the aggregate in saturated lime water and covering the surface with calcium oxide powder has better effects in all aspects. Compared with the comparative example, the permeability coefficient and continuous porosity changes of Example 1 are improved. This shows that the added cellulose ether, defoamer and latex powder have the effect of increasing the pores of the permeable concrete, which can make CO2 contact with the permeable concrete more fully. In addition, it was found that the compressive strength and flexural strength were improved to a certain extent, among which the increase in compressive strength was 102.0%. The strength of the aggregate is improved in two aspects: on the one hand, after the aggregate is soaked in saturated lime water, the surface is covered with calcium hydroxide, and calcium carbonate is generated after contacting with carbon dioxide during the carbonization process; on the other hand, the surface of the aggregate is covered with calcium oxide powder, and calcium oxide reacts with water to generate calcium hydroxide, which provides sufficient conditions for subsequent carbonization. The improvement in strength shows that the treatment of recycled aggregate has a positive effect on carbon fixation in permeable concrete, the carbonization efficiency is effectively improved, and the effect of improving the strength of concrete is better.
[0052] Table 2
[0053] The present invention provides an idea and method for early-strength, fast-hardening, efficient carbon-fixing, regenerated permeable concrete and its preparation method. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. An early-strength, fast-hardening, efficient carbon-fixing and regenerating permeable concrete, characterized in that: Made from the following components in parts by mass: 100~160 parts of recycled aggregate, 30~40 parts of binder, 18~19 parts of water, 0.36~1.08 parts of cellulose ether, 0.36~0.72 parts of defoamer, 0.36~3.6 parts of dispersible latex powder and 1.8~2.88 parts of early strength seed; The binder is composed of ordinary Portland cement and sulphoaluminate cement in a mass ratio of 2 to 3:1; The mass ratio of the recycled aggregate to the binder is controlled at 3-5:
1.
2. The early-strength, fast-hardening, efficient carbon-fixing and regenerating permeable concrete according to claim 1, characterized in that: The recycled aggregate is crushed recycled concrete aggregate, the particle size of the recycled aggregate is between 5 and 16 mm, and the preparation method is: The waste concrete aggregate is crushed and ground, passed through a square hole sieve with an aperture of 4.75-9.5 mm, and then placed in saturated lime water until the saturated surface is dry. Subsequently, the surface-dry concrete aggregate is placed in calcium oxide powder and mixed thoroughly so that the surface of the concrete aggregate is evenly covered with calcium oxide.
3. The early-strength, fast-hardening, efficient carbon-fixing and regenerating permeable concrete according to claim 1, characterized in that: The ordinary Portland cement is graded P.Ⅱ 52.5R and has a specific surface area of 300-400 m 2 kg -1 The sulphoaluminate cement has a grade of 525 and a specific surface area of 400-500 m 2 kg -1 .
4. The early-strength, fast-hardening, efficient carbon-fixing and regenerating permeable concrete according to claim 1, characterized in that: The cellulose ether is hydroxyethyl methyl cellulose, with a viscosity of 35000-45000 MPa·s and an average particle size of 10-12 μm.
5. The early-strength, fast-hardening, efficient carbon-fixing and regenerating permeable concrete according to claim 1, characterized in that: The defoamer is a silicone modified defoamer, model RE 2971, in the form of milky white powder with an average particle size of 18-20 μm.
6. The early-strength, fast-hardening, efficient carbon-fixing and regenerating permeable concrete according to claim 1, characterized in that: The dispersible latex powder is ethylene-vinyl acetate latex powder, which is in the form of white powder with an average particle size of 80-90 μm.
7. The early-strength, fast-hardening, efficient carbon-fixing and regenerating permeable concrete according to claim 1, characterized in that: The early strength seed crystal is a CSH seed crystal suspension, the calcium-silicon molar ratio is 0.9-1, and the solid content of the suspension is 20-25wt%.
8. The method for preparing the early-strength, fast-hardening, efficient carbon-fixing and regenerating permeable concrete according to claim 1, characterized in that: The steps include: (1) After sieving the waste concrete aggregate, place it in saturated lime water until the saturated surface is dry, then place the surface-dry concrete aggregate into calcium oxide powder and mix them thoroughly so that the surface of the concrete aggregate is evenly covered with calcium oxide to obtain recycled aggregate; (2) mixing ordinary Portland cement and sulphoaluminate cement uniformly to obtain a binder; (3) Mix the binder and 1 / 2 to 2 / 3 of the total water volume and stir evenly, then add cellulose ether, dispersible latex powder and early strength seed crystals in sequence, and continue stirring for 1 to 5 minutes; (4) Add the remaining water and recycled aggregate, mix well, put into the mold, vibrate and compact, and transfer the mold into a closed curing room for curing for 6 to 12 hours; (5) After the curing is completed, the mold is removed and the specimen is placed in a carbonization kettle and carbonized by introducing carbon dioxide gas. After the carbonization is completed, the specimen is placed in water for curing.
9. The method for preparing the early-strength, fast-hardening, efficient carbon-fixing and regenerating permeable concrete according to claim 8, characterized in that: In step (4), the relative humidity in the closed curing room is 90-100% and the temperature is 18-22°C.
10. The method for preparing the early-strength, fast-hardening, efficient carbon-fixing and regenerating permeable concrete according to claim 8, characterized in that: In step (5), the mass fraction of carbon dioxide gas in the carbonization kettle is 90-100%, the carbonization pressure is 0.3-0.8 MPa, and the carbonization time is 2-6 h.
Citation Information
Cited By
Method for curing cement concrete product through CO2 reverse carbonization
CN119330748A